Kelarutan Zat Warna Organik Dalam Gelasi Mikroemulsi Water In Oil Sistem Air, Surfaktan Kationik (Hexadecyl Trimethyl Ammonium Bromide) dan Pentanol - Pamela Jurdilla; Ananda Putra (Departemen Kimia FMIPA UNP, 2022)
Research on the solubility of organic dyes in gelation microemulsion water in oil (w/o) water system, cationic surfactant (Hexadecyl Trimethyl Ammonium Bromide) and pentanol aims to prepare gels from microemulsion (w/o) using the sol-gel method by adding TEOS and ethanol in a ratio of 1:8 mol which hydrolyzed with water to form a gel, the percentage of organic dye solubility of turmeric powder at pH 4,5 and 9,5 3,92% and 3,95% then dragon fruit peel powders 1,96% and 1,93% at pH 4,5 and 9,5. Respectively, density testing can be carried out to see the concentration of the dye with greatest value that is turmeric powder 0,8677 g/cm3 and 0,8684 g/cm3 for pH 4,5 dan 9,5. Measurement of refractive index to see the homogeneity of the largest solution is turmeric at pH 4,5 and 9,5 namely 1,4014 and 1,4024.